2021
DOI: 10.1136/bmjopen-2021-049069
|View full text |Cite
|
Sign up to set email alerts
|

Association between participation in the government subsidy programme for domestic travel and symptoms indicative of COVID-19 infection in Japan: cross-sectional study

Abstract: ObjectiveTo investigate the association between participation in government subsidies for domestic travel (subsidise up to 50% of all travel expenses) introduced nationally in Japan on 22 July 2020 and the incidence of symptoms indicative of COVID-19 infections.DesignCross-sectional analysis of nationally representative survey data.SettingInternet survey conducted between 25 August and 30 September 2020 in Japan. Sampling weights were used to calculate national estimates.Participants25 482 survey respondents (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 23 publications
(13 reference statements)
3
53
0
Order By: Relevance
“…We analyzed data from the Japan "COVID-19 and Society" Internet Survey (JACSIS) study [26], a cross-sectional, web-based, self-reported questionnaire survey administered by a major nationwide internet research agency with 2.2 million qualified panelists [27][28][29]. Selected individuals aged 15 to 79 years (n=224,389) were included in the JACSIS study using stratified random sampling based on gender, age, and prefecture category to represent the distribution of the general population in Japan in 2019 [30,31]. Individuals who agreed to participate in the survey accessed the designated website and responded to questionnaires asking about a wide range of socioeconomic, lifestyle, and health measures in the context of the COVID-19 pandemic.…”
Section: Study Design Setting and Data Sourcesmentioning
confidence: 99%
“…We analyzed data from the Japan "COVID-19 and Society" Internet Survey (JACSIS) study [26], a cross-sectional, web-based, self-reported questionnaire survey administered by a major nationwide internet research agency with 2.2 million qualified panelists [27][28][29]. Selected individuals aged 15 to 79 years (n=224,389) were included in the JACSIS study using stratified random sampling based on gender, age, and prefecture category to represent the distribution of the general population in Japan in 2019 [30,31]. Individuals who agreed to participate in the survey accessed the designated website and responded to questionnaires asking about a wide range of socioeconomic, lifestyle, and health measures in the context of the COVID-19 pandemic.…”
Section: Study Design Setting and Data Sourcesmentioning
confidence: 99%
“…Detailed methods (eg, participation rate and data management) are presented in the previous study. 38 …”
Section: Methodsmentioning
confidence: 99%
“…Propensity scores were calculated by logistic regression analysis using sex, age and socioeconomic factors to adjust for differences between a current and population-based sample from the Comprehensive Survey of Living Conditions of People on Health and Welfare 2016. Detailed methods (eg, participation rate and data management) are presented in the previous study 38…”
Section: Methodsmentioning
confidence: 99%
“…Among the 28 000 participants in the JACSIS, 25 482 participants remained after excluding 2518 participants whose data showed discrepancies and/or artificial/unnatural responses. Three question items namely ‘choosing the second from the bottom’, ‘choosing the positive options in a set of questions on drug use’ and ‘choosing the positive options in a set of questions on current chronic diseases’ were used to detect any discrepancies 23 24. After further excluding current cigarette smokers (n=3403), current HTP users (n=2082), non-workers (work-at-home people, students, retired people, housewives/husbands and people out of jobs) (n=10 116), those who did not go to their workplaces (n=6997) and those whose workplace smoke-free policies were unknown (n=1628), 8196 respondents remained for the analysis.…”
Section: Methodsmentioning
confidence: 99%